Disfungsi Seksual pada Pasien Gagal Ginjal Kronis - Akhyarul Anam; Sahrudi Sahrudi (Jurnal Surya Medika (JSM), 2020)
Chronic kidney failure affects sexual function problems (sexual dysfunction) which tends to worsen with decreased kidney function. This study aimed to explore in-depth the response of individuals in dealing with sexual dysfunction. This study used qualitative research methods and case study approach with a single case design through semi-structured interviews. Samples were taken by purposive sampling technique in patients with chronic kidney failure who experience sexual dysfunction. Data is processed by the thematic content analysis method. The main themes found include erectile dysfunction, actions taken for sexual dysfunction problems, responses to the face of sexual dysfunction, as well as expectations for health services. Traditional alternative therapy is done, but there are no significant results. Participants' response is positively such as giving in, increasing spiritual activity, and being aware of old age. Health services for sexual dysfunction problems are highly expected.